Modeling and dynamic simulation of activated sludge process in sequencing batch reactor - Azwar, -; Hussain, Mohd Azlan; Ramachandran, K.B. (Curtin University of Technology, 2005)
This paper presents the results of a modeling and simulation study of an activated sludge process in a sequencing batch reactor (SBR), with emphasis on total nitrogen removal. This study focuses on the effect of dissolved oxygen (DO) and the phase length of aeration on the effluent chemical oxygen demand (COD) and nitrogen removal in SBR, so that the effluent COD and nitrogen removal can be maintained at the desired values. Simulation results show that operation of a SBR can be optimized by adjusting the DO set point, and that there is a close relationship between the DO concentration and respiration rate.